2014
DOI: 10.1007/s10103-014-1673-6
|View full text |Cite
|
Sign up to set email alerts
|

Low power laser stimulation of the bone consolidation in tibial fractures of rats: a radiologic and histopathological analysis

Abstract: The objective of this study is to analyze the effectiveness of low power laser irradiation in the bone consolidation of tibial fractures in rats. An experimental, comparative, prospective study with control group was designed. Twenty Wistar rats were grouped into control (n = 10) and experimental groups (n = 10). A tibial fracture, with a mechanical drill, was inflicted in all rats. The experimental group received ten days of low power arsenide-gallium laser irradiation of 850 nm (KLD, Sao Paulo, Brasil)-100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…This study used alveolar bone after tooth extraction in rats as a model to evaluate the effect of LLLT and cigarette smoke exposure on bone metabolism and bone turnover. LLLT consists of non-thermal irradiation at wavelengths between visible light and the nearinfrared range; the irradiated cells absorb the light, triggering intracellular signaling cascades that can lead to various biological effects (20), such as cell growth, proliferation and differentiation. It has been shown that LLLT accelerates the process of wound healing (12,13,18,20), increases blood flow and it promotes the release and secretion of vascular growth factor related to angiogenesis (12) allowing a more adequate supply of oxygen and nutrients to guarantee the needs of the proliferative phase in the healing process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study used alveolar bone after tooth extraction in rats as a model to evaluate the effect of LLLT and cigarette smoke exposure on bone metabolism and bone turnover. LLLT consists of non-thermal irradiation at wavelengths between visible light and the nearinfrared range; the irradiated cells absorb the light, triggering intracellular signaling cascades that can lead to various biological effects (20), such as cell growth, proliferation and differentiation. It has been shown that LLLT accelerates the process of wound healing (12,13,18,20), increases blood flow and it promotes the release and secretion of vascular growth factor related to angiogenesis (12) allowing a more adequate supply of oxygen and nutrients to guarantee the needs of the proliferative phase in the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…LLLT consists of non-thermal irradiation at wavelengths between visible light and the nearinfrared range; the irradiated cells absorb the light, triggering intracellular signaling cascades that can lead to various biological effects (20), such as cell growth, proliferation and differentiation. It has been shown that LLLT accelerates the process of wound healing (12,13,18,20), increases blood flow and it promotes the release and secretion of vascular growth factor related to angiogenesis (12) allowing a more adequate supply of oxygen and nutrients to guarantee the needs of the proliferative phase in the healing process. On the other hand, nicotine and other toxic substances found in cigarette smoke (19,21) promote inhibition of bone repair after guided bone regeneration and inhibit the expression of many cytokines including those associated with neovascularization (21), and osteoblastic differentiation (22).…”
Section: Discussionmentioning
confidence: 99%
“…33 Yamada demonstrated that LLLT was able to induce proliferation and differentiation of osteoblastic cells in vitro. 34 The consideration of this type of evidence and the recurrent investigation of the effects of lasers on experimental bone healing 11,35 led us to test the hypothesis that LLLT could have an effect enhanced by the biomodulatory properties of methylene blue.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that PBM stimulates cytochromes responsible by increasing ATP production and consequently, cellular activity 20,21,27 . Specifically for bone tissue, PBM induces the differentiation of mesenchymal cells into pre‐osteoblasts and osteoblasts and fibroblasts, 57,58 produces neoangiogenesis 58,59 and increase the deposition newly formed bone 60,61 . Furthermore, Table 4 demonstrated that the use infrared wavelength is a consensus among authors (the only exception is the study of Asanami, et al 37 ), once it is widely known that infrared range is more effective to stimulate bone because longer wavelengths reach deeper tissues 62,63 .…”
Section: Discussionmentioning
confidence: 99%